2001
DOI: 10.1002/ccd.10045
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the perclose suture–mediated closure device after diagnostic and interventional catheterizations in a large consecutive population

Abstract: Arterial puncture sites after cardiac catheterization are a troublesome cause of complications. Closure devices have been developed to improve on patient comfort and safety. We evaluated a suture-mediated closure device, the Prostar-Plus device, in a consecutive population of over 10,001 diagnostic and interventional catheterizations. A significantly higher complication rate was noted for both major and minor complications in the diagnostic catheterization patients treated with the Prostar-Plus device compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 9 publications
2
49
0
1
Order By: Relevance
“…The number of enrolled patients in the studies ranged from 60 to 10,001 (8,34), with 57% of studies having Ն100 patients in each arm. In all studies, most patients were men (range 56% to 94%) (5,8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of enrolled patients in the studies ranged from 60 to 10,001 (8,34), with 57% of studies having Ն100 patients in each arm. In all studies, most patients were men (range 56% to 94%) (5,8).…”
Section: Resultsmentioning
confidence: 99%
“…Studies assessing Angio-Seal (Angio-Seal Daig, Minnetonka, Minnesota) (3,6,9,11,12,(17)(18)(19)(20)(21)(22)(23), VasoSeal (VasoSeal Datascope Inc., Montvale, New Jersey) (4,5,19,24 -30), and Perclose (ProStar Plus or TecStar; Perclose, Redwood City, California) (7,8,10,12,13,18,19,21,23,29,(31)(32)(33)(34)(35) were included in the meta-analysis. Data on various devices as well as on diagnostic (Dx) catheterization and PCI were assessed separately and in combination.…”
Section: Methodsmentioning
confidence: 99%
“…Three different devices are currently FDA-approved: the AngioSeal (St. Jude Medical), which sandwiches an intraarterial absorbable anchor on the luminal side of the vessel and a thrombin plug on the surface of the vessel using a self-cinching stitch [1]; the Vasoseal (Datascope, Montvale, NJ), which deposits a thrombin plug directly over the femoral artery puncture site [3]; and Perclose device (Perclose, Redwood City, CA), which uses a percutaneous means directly to suture and close the femoral artery puncture site [4]. While all three devices have been shown to reduce time to hemostasis, their rates of access site complication are similar to or greater than manual compression [2,4,5]. However, one study did show that in those patients on IIb/IIIa receptor antagonists, there were less complications in those patients who received closure devices rather than manual compression [6].…”
Section: Discussionmentioning
confidence: 99%
“…3 In a retrospective trial that reported a higher overall complication rate in 10,001 device-treated patients, reported complications were hematomas (10.5%), pseudoaneurysms (2.7%), a need for transfusions (1.3%), and a requirement for surgical pseudoaneurysm repair (0.67%). 4 Another study reported that surgical repair was necessitated in 0.3% of cases after the use of arterial closure devices. 5 In addition to hematomas and pseudoaneurysms, other injuries have been described in patients treated with arterial closure devices, including arterial dissection, arterial occlusion, and retained devices, [5][6][7][8] but the overall incidences of these complications are difficult to extrapolate from the small sample sizes presented.…”
Section: Discussionmentioning
confidence: 99%